Jessica + Jessica = trouble - Stewart, Molly Mia; Pascal, Francine Hu, Ying-Hwa (Bantam Books New York, 1995)
There's a new girl in Mrs. Otis's class -- and her name is Jessica! At first Jessica Wakefield thinks it will be fun to share her name with a friend. But soon Jessica realizes that the new girl doesn't want to be friends -- she just wants to be better than the old Jessica at everything. She even tries to steal Jessica's own sister, Elizabeth! Is Sweet Valley Elementary big enough for two Jessicas?